The Qualified Employee in the Digital Age: Challenges and Opportunities - mohamed maamerie (Sociedad & Tecnología)
This study aimed to explore the impact of digital qualification on job performance and innovation at the Main Public Library in Djelfa Province. Interviews were used as a data collection tool from a sample of 8 employees. The study found that digital skills are a critical factor in improving productivity; however, the lack of resources and administrative support poses a barrier to achieving the required digital qualification. The findings also showed that digital qualification significantly contributes to increasing innovation, but challenges related to training and resource availability hinder this progress.